Malignant Lymphoma in the Parasellar Region - Takao Koiso; Hiroyoshi Akutsu; Shingo Takano; Tetsuya Yamamoto; Eiichi Ishikawa; Yasushi Okoshi; Akira Matsumura (Case Reports in Medicine)
The entity of pituitary (sellar or parasellar) lymphoma includes primary pituitary lymphoma (PPL) and secondary pituitary lymphoma (SPL). The latter has an involvement of systemic lymphoma. Both of these lymphomas are extremely rare. We describe a patient with SPL showing a good prognosis. A 78-year-old woman presented with diplopia, left ptosis, and back pain. Magnetic resonance (MR) imaging revealed a parasellar mass lesion extending to the upper clivus and another mass lesion with compression fracture of the Th3 vertebral body. Transsphenoidal exploration was performed, and it showed diffuse large B-cell lymphoma. Based on the positive tumor cells in the following bone marrow aspiration and hepatosplenomegaly in computed tomography (CT) findings, this patient was diagnosed as having a pituitary involvement of systemic lymphoma. After chemotherapy, she achieved complete remission for 4 years. The entity of pituitary lymphoma is extremely rare. Nineteen cases of PPL and 16 cases of SPL have been reported. Generally, clinical and radiological diagnosis was difficult because there are no specific findings. Therefore, biopsy was necessary in all of the cases. T2 hypointensity of a lesion in MR imaging in addition to an elevated serum level of soluble interleukin-2 receptor (sIL-2R) in a patient with a sellar lesion can be useful clues for the differential diagnosis of this rare disease.